Metformin improves pregnancy outcomes in non-PCOS women with insulin resistance and recurrent implantation failure before frozen embryo transfer - Peng, Liying; Yang, Wanli; Du, Mengyang; Deng, Xujing; Zhang, Ruixiu; Qin, Dengke; Bao, Shihua (Frontiers in Endocrinology, 2025)
BackgroundRecurrent implantation failure (RIF) leads to a significant waste of embryos and imposes substantial physical, emotional, and financial stress on patients. Given its complex and diverse etiology, identifying the underlying causes and developing effective interventions are crucial. Previous studies have shown that insulin resistance (IR) has negative effects on reproductive health, and metformin pre-treatment helps improve the pregnancy outcomes in IR patients. However, its role in patients with RIF remains unclear, especially in those without polycystic ovary syndrome (PCOS).MethodsA retrospective cohort study was conducted. The FET cycles of RIF patients without PCOS were stratified based on the presence or absence of IR. We used the univariate and multivariate generalized estimating equations (GEE) analysis to compare pregnancy outcomes between patients with IR and without IR, as well as between metformin-exposed and metformin-unexposed groups of RIF patients with IR.ResultsIn a subgroup of 941 cycles without IR and 145 cycles with IR, we found that patients with IR had a lower live birth rate (10.34% vs 20.94%, P = 0.0039) and a higher early miscarriage rate (52.77% vs 27.52%, P = 0.0034). After adjusting for potential confounders, the IR group still had a lower live birth rate (aOR = 0.5, 95% CI: 0.28-0.89, P = 0.019). In the subgroup of IR patients (n=330 cycles), patients in the metformin-exposed group (n=185 cycles) had a higher clinical pregnancy rate (43.24% vs 24.83%, P < 0.001), implantation rate (33.22% vs 17.04%, P < 0.001) and live birth rate (33.51% vs 10.34%, P < 0.001), as well as a lower early miscarriage rate (12.50% vs 52.78%, P < 0.01), compared to the metformin-unexposed group (n=145 cycles). These differences remained significant after adjusting for potential confounders using GEE analysis.ConclusionsOur results demonstrated that IR may be a risk factor for a low live birth rate in RIF patients without PCOS. However, the negative impact of IR on the live birth rate can be alleviated by metformin pre-treatment before FET cycles.